PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH MELALUI CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI PADA MAHASISWI S1 AKTIF FISIP UNDIP) - Elma Sintya Sendi Pertiwi; Ari Pradhanawati (Universitas Diponegoro, 2020)
The model of this research is testing the influence of product quality and advertising to purchase decisions Wardah brand cosmetics through brand image as an interveving variable. The population on this study were consumers of Wardah cosmetics on students collage faculty political and social science of Diponegoro University. The research sample of 98 respondens and the sampling technique used was propotional sampling.Measurement scala using a Likert scale. Data analysis used regression test, correlation test, determination test, significance test, path analysis, sobel test and mediation test with SPSS version 16 aplication. The results of this study note that the quality of the product significantly influences the brand image with the value of t arithmetic (6.905)> t table (1.985), it is proven that there is a significant influence of advertising with brand image with the value of t arithmetic (6.346)> t table (1.985), proved the influence Significant product quality with a purchase decision (5,967)> t table (1,985), evidenced by the significant influence of advertising with a purchasing decision with a value of t arithmetic (3.685)> t table (1,985), evidenced the influence of brand image with a purchase decision t arithmetic (5,951) )> t table (1,985), it is proven that there is a significant influence between product quality on purchasing decisions through brand image with a value of t arithmetic (2,930)> t table (1,985) and evidenced the influence of advertising on purchasing decisions through a brand image with a value of t arithmetic (3,663)> t table (1,985).